COFFEE AND IDENTITY: Consume Coffee, Build Identity, Maintain Variety on Palintang Community West Java - Rahman Latif Alfian; Budiawati Supangkat; Johan Iskandar (Universitas Padjadjaran, 2020)
This article discusses the Palintang coffee and its social, cultural and ecological impacts on the people of the Palintang Hamlet. Palintang hamlet is located in directly adjacent to the forest under the management of the State Forestry Corporation (Perhutani). Last fifteen years, the government began to intensify the cultivation of coffee plant in the Palintang hamlet. Palintang hamlet is located approximately 1,400 above sea level. As a result, coffee of Arabica plant (Coffeea arabica L) grows well in the area. The purpose of this article is to elucidate at the impact of coffee on the social identity of the Palintang community. The method used in this study was ethnographic approach which aims to reveal meaning from the point of view which of cultural stakeholders. Some field research techniques, namely observation, deep interviews, and participant observation were applied in this study. The results of this study showed that the coffee cultivation in Palintang hamlet has been an important impact not only an economic, but also social and ecological aspects of the Palintang community. The community always highlight the distinctive characteristics of the Palintang coffee, even some people claim that Palintang coffee has a characteristic that no other coffee has. This process then makes coffee as one of the markers for the community of Palintang, because through coffee of the community members are known to other community groups. The distinctive characteristic of Palintang coffee also adds to the repertoire of varieties of archipelago coffee, especially those related to the character of coffee.